Accelerating Transformation Program in Indonesian Regional Development Banks: The Importance of High-Quality Information - Fettry, Sylvia; Djajadikerta, Hamfri; Lusanjaya, Gery Raphael (Journal of Accounting Research, Organization and Economics, 2018)
Objective The role of Indonesia Regional Development Bank (RDB) as an agent of development in each specific operational area is expected to give a significant contribution to regional economics. The Transformation Program in Indonesian RDB started since 2015 is created to optimize the RDBs role. This study is aimed to gain some description about the level of information quality in Indonesian RDB, to obtain real situation on the implementation of Transformation Program in Indonesian RDB, and to test whether the high-quality information will accelerate the implementation of Transformation Program in Indonesian RDB.Design/methodology The study was conducted using data from the annual report of Indonesian RDBs and additional in-depth interview with RDB practitioners. The technique of purposive sampling is used in this study with the data availability criteria. The statistic analysis uses multiple regression with t-test and F-test to test the influence of information quality and some control variables on the implementation of Transformation Program in Indonesian RDB.Results The Indonesian RDBs quality of information still cannot be perceived at a high level. The implementation of Transformation Program in Indonesian RDBs has already run in the first phase of foundation building with various obstacles. The high-quality information produced by financial reporting of RDB is proven can accelerate the implementation of Transformation Program in Indonesian RDBs.Research limitations/implications The theoretical contribution of this study is giving empirical evidence that the information quality accelerates the implementation of Transformation Program in Indonesian RDB. The managerial implication is that Indonesian RDBs must improve their financial reporting system and create some innovations for the successful Transformation Program. The main limitation of this research is the limited scope of study. It is recommended to make further relevant research on the same issue in a wider context to get more enriched findings.Novelty/Originality The area of implementation of Transformation Program in Indonesian RDBs has been insufficiently examined currently. Thus, this study contributes to this area by examining whether high-quality information produced by financial reporting will accelerate the implementation of Transformation Program in Indonesian RDB.Keywords Information Quality, Financial Reporting, Banking Transformation.